ENGLISH FOR ACADEMIC PURPOSES: CASE STUDIES IN EUROPE - George S. Ypsilandis; Z. Kantaridou (Revista de Lingüística y Lenguas Aplicadas)
This study attempts to provide some insights into current practices in the teaching of English for Academic Purposes (EAP) in Europe, and through a set of parameters relating to research in the area: (a) to initially analyse data resulting from a survey concerning the teaching of EAP in several universities, in relation to basic trends in English Language Teaching (ELT) in general and the teaching of EAP in particular and, (b) to provide suggestions for improvements in the educational approach and the academic content, as well as in the administrative aspects of the teaching of EAP in Europe. For this purpose, it seemed necessary to briefly review the relevant literature related to these basic trends and, further, analyse the present EAP situation in a number of European universities. We trust that our suggestions will be of value to those involved in the teaching of EAP in Europe and other places with similar conditions and help promote both teaching effectiveness and the quality of learning.